Design Model For The Development Of Agroeducational Tourism Area Based On Integrated Fisheries In Kalisentul, Kulon Progo - Resna Trimerani; Alan Handru (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: To apply an integrated fisheries model to Kalisentul Agrotourism as an educational medium, and to determine the involvement of community groups in the management of Kalisentul Agrotourism as an agricultural and fisheries education-based Agrotourism. Methodology: Using a qualitative descriptive method with data collection through observation and in-depth interviews. The method in empowering the community uses the Participatory Rural Appraisal (PRA) approach. Results: The application of the educational development model in Kalisentul Agrotourism is based on the Integrated Fisheries field which is realized in the form of Aquaponics system cultivation, where this cultivation system combines fish and vegetable cultivation activities in one circulation of nutrients and waste utilization. In addition, the involvement of community groups, both farmer groups, women's farmer groups and fish farming groups shows that they really appreciate this development model. Findings: The important result of this study is that the development of an Agrotourism Area based on agricultural and fisheries education can have a positive impact on the environment, society and Agrotourism management because they are mutually sustainable. Novelty: Implementing an Integrated Farming model for education-based agrotourism in Kalisentul, involving community groups in its development. Originality: This research focuses on the application of education in agrotourism through an Integrated Farming System involving community groups consisting of Farmer Groups, Women Farmer Groups, and Fish Farmer Groups. Furthermore, the integrated system will have a positive impact on environmental aspects and community empowerment. Conclusion: The integrated fisheries system, namely implementing an aquaponic cultivation system with the development of Azolla cultivation as a complement to the Integrated Farming system, has also been demonstrated. Furthermore, there has been positive involvement and response from community groups in managing and developing Kalisentul Agrotourism into an education-based agrotourism area.Type of Paper: Research article.